CircMIB1 inhibits glioma development and progression through a competing endogenous RNA interaction network - Chen, Simin; Li, Longping; Xu, Wei; Xie, Nanjiao; Xu, Huiting; Zhou, Yongjun; Zou, Ying; Yi, Kai; Zhang, Zuping (Frontiers in Molecular Biosciences, 2024)
IntroductionThe critical role of circular RNAs as non-coding RNAs in glioma has been extensively investigated. Therefore, we aimed to explore the role and potential molecular mechanisms of circRNA-mind bomb homolog 1 (circMIB1) in gliomas.MethodsRNA sequencing was used to analyze the expression profiles of circRNAs in glioma tissues and normal brain tissues. Quantitative real-time polymerase chain reaction was implemented to examine the levels of circMIB1 in glioma cells and tissues. The circMIB1 was identified as a cyclic RNA molecule by DNA nucleic acid electrophoresis and ribonuclease R assay. The relationship between circMIB1 expression and the prognosis of glioma patients and its potential as a biomarker were analysed using Kaplan-Meier, Receiver operating characteristic curves, and Principal component analysis. Bioinformatics analysis predicted the miRNAs that bind to circMIB1 and their downstream targets, and analysed the functions of these genes.ResultsFirstly, a novel circRNA molecule termed circMIB1 was identified and validated by RNA sequencing. The expression of circMIB1 was significantly downregulated in glioma cells and tissues, and was closely associated with the tumor grade and survival prognosis of patients with glioma. Hence, it may be useful as a biomarker for glioma. Secondly, it was predicted that circMIB1 binds to hsa-miR-1290 based on bioinformatics analysis, which was significantly upregulated in glioma cells and tissues, and correlated with the tumor grade and overall survival of patients. Thirdly, through a series of bioinformatics analyses identified six genes downstream of hsa-miR-1290 that were significantly associated with glioma expression and prognosis, these genes are associated with cell cycle, cell necrosis and cell circadian rhythms.DiscussionCircMIB1 may play a role in inhibiting glioma development through the hsa-miR-1290 competitive endogenous RNA interaction network, these findings provide new ideas and directions for the diagnosis and treatment of glioma.